Chemical variability in essential oils from Ruta species among seasons, and its taxonomic and ecological significance. Issue 19 (2nd October 2017) - Bennaoum, Zineb; Benhassaini, Hachemi; Falconieri, Danilo; Piras, Alessandra; Porcedda, Silvia
Abstract: Leaf essential oils of 11 samples from Ruta montana, Ruta chalepensis subsp. latifolia and Ruta chalepensis subsp. angustifolia collected from two sites have been studied by GC/MS that allowed to identify 22, 25 and 12 components, respectively. The variability in the composition of essential oils among species and seasons was very high, and hence the existence of different chemotypes has been inferred. The major components were 2-undecanone, (E) caryophyllene, 2-nonanone and 2-methyloctyl acetate. Multivariate analysis of the 11 samples suggest that the main factors capable to influence the chemical composition of leaf essential oils was both the collection period and the geographical origin. 2-Undecanone seems to be the chemotaxonomic marker of Ruta genus. Furthermore, the formation of distinct clusters and sub-clusters at high distance also supports that the patterns of distribution of chemical constituents among seasons can be used in delimiting species and infraspecific taxa within the species complexes. Abstract :